Optimization of TPACK-Based Project Learning in Micro Teaching Courses in the Mathematics Education Study Program - Nuraina Nuraina; Rahmi Hayati; Rohantizani Rohantizani; M Mursalin; Muliana Muliana; Ratna Unaida (SAINTIS Publishing, 2025)
The purpose of this research is to optimize project learning based on Technological Pedagogical Content Knowledge (TPACK) in the Micro Teaching course in the Mathematics Education Study Program. A descriptive qualitative approach is used to describe student involvement in each stage of the project: starting from planning, digital media development, implementation of micro teaching, reflection, revision, to publication of results. Data was collected through observations, project documents, and assessment sheets based on the TPACK rubric. The results showed that students were able to integrate elements of technology, pedagogy, and content quite well, with the highest scores in the Pedagogical Knowledge (4.5) and TPACK (4.4) dimensions, and the lowest scores in the Technological Content Knowledge dimension (4.1). These findings show that the TPACK-based project learning model is effective in developing the competencies of prospective 21st century mathematics teachers who not only master the material and learning strategies, but are also able to utilize technology appropriately. This study recommends the sustainable application of similar models to support the transformation of digital-based education and innovative pedagogy in higher education.